Comparison of patient satisfaction with diode laser treatment of female hirsutism: low fluence or high fluence?. (18th August 2021) - Ebrahimzadeh Ardakani, Mohammad; Azad, Mehran; Ghanei, Narges; Etaee, Farshid; Naguib, Tarek; Daveluy, Steven
ABSTRACT: The optimal fluence for treating hirsutism with the diode laser has not been elucidated. The aim of this study is to evaluate and compare the satisfaction and side effects of patients who have been treated with two diode laser therapy techniques: high-fluence and low-fluence. In this cross-sectional study, the medical records of 182 patients referred to Yazd Laser center were collected. Various side effects of laser therapy were assessed, and the satisfaction rate of the patients was evaluated at three points: after the first session, at the end of the treatment course, and six months after the end of the treatment. The satisfaction level after the first session of the laser treatment was higher with the low-fluence technique ( P -value<0.001). The satisfaction level at the end of treatment was the same in the two groups ( P -value = 0.394). However, six months after the treatment, satisfaction level was significantly higher with the low-fluence technique ( P -value = 0.005). The rate of complications, such as burn and pain, was higher in the high-fluence group, while the number of treatment sessions was lower with the high-fluence technique. The low-fluence method of laser therapy has fewer complications associated with greater patient satisfaction.